The long-term performance of post-merger and acquisition: evidence from Indonesia's stock market. (13th July 2022) - Tarigan, Josua; Evania, Jacqueline; Devie, Devie; Hatane, Saarce Elsye
This study evaluates the long-term share performance of firms over three years after they underwent merger and acquisition (M&A). This is happening since researchers failed to find answers in the short-term analysis and began looking for answers through long-term analysis. Most previous studies have been done either in big capital markets (US and the UK) or smaller capital markets such as Greece and Malaysia but not Indonesia. The share performance was measured through cumulative market adjusted abnormal return (CMAR) and buy and hold abnormal return (BHAR). The result of this study provides evidence of the presence of negative abnormal returns of the merged and acquiring firms. Moreover, the results show that cash payments are preferable in comparison to the share settlement. The results also reveal that the firms which are owned by families tend to outperform the firms which are not owned by families.